MANAGEMENT AND INTERACTION CORRELATION - G. Avetisayn (Вестник университета)
The article presents classification of interaction by types of management, and also presents correlation of the concepts of interaction of organizations in management and interaction management of organizations. Approaches to the definition of the concepts under consideration to the energy sector of the participated in the Eurasian Economic Union countries are researched, and authorial arguments in favor of the prevailing position of interaction management of organizations in modern science are proposed.